Nghiên cứu xác định dạng tồn tại của asen (As) trong đất, rau má (Centella asiatica) và cải xanh (Brassica juncea) bằng phương pháp quang phổ hấp thu nguyên tử (AAS) kỹ thuật hydrua hóa (HG) - Kim Phượng, Nguyễn Thị; Dung, Nguyễn Thị; Liên, Ngô Kim (Vietnam Journal of Chemistry, 2014)
Due to the high toxicity of arsenic and the poison effects to human being, identification and quantification of individual arsenic forms are important to appropriately measure the arsenic toxicity, environmental impact and health risk related to arsenic exposure. Arsenic species were quantified by HPLC-UV-HG-AAS. The separation was performed on an anion exchange Hamilton PRP-X100 (250 mm×4,1 mm i.d.×10 µm) column by using mobile phase A: 12 mmol/l KH2PO4-K2HPO4; pH = 6.5 and B: 24 mmol/l KH2PO4-K2HPO4; pH = 6. The detection limits of arsenic species (As3+, DMA, MMA, As5+) with HPLC-UV-HG-AAS system was 5 ppbAs. The results indicated that arsenic presented in soil solution is arsenate As(V) and no methylation of arsenic taken place in the soil. There is a reduction of As(V) to As(III) in the root of Pennywort and Cabbage. Arsenic accumulation in the root of these plants was As(III) and no methylation of arsenic taken place in these plants